PENGARUH PENGGUNAAN MODEL DISCOVERY LEARNING BERBANTUAN MEDIA AUDIOVISUAL TERHADAP KETERAMPILAN MENULIS TEKS BERITA SISWA KELAS VII SMP NEGERI 42 PADANG - Beby Ratrika Ayu; Yulianti Rasyid (EDU RESEARCH, 2025)
This study uses a method with a One Group Pretest-posttest Design research design. The population of this study was 131 students of class VII of SMP Negeri 42 Padang. The research sample was selected based on purposive sampling technique. The sample used was only one class, namely class VII.1. Based on the t-test, the alternative hypothesis (H1) was accepted at the level of confidence and degrees of freedom (dk) = (n-1) because tcount> ttable (4,53 > 1.67). Thus, the learning outcomes of news text writing skills of class VII students of SMP Negeri 42 Padang who used the Discovery Learning model assisted by audiovisual media were higher than those who used the conventional model. Based on the results of the study, it can be concluded that the Discovery Learning model assisted by audiovisual media has an effect on the news text writing skills of class VII students of SMP Negeri 42 Padang.